PENGARUH SUHU PEMANASAN FORMALIN 10% TERHADAP PERKEMBANGAN TELUR Ascaris lumbricoides - Ni Putu Aryadnyani (Meditory : The Journal of Medical Laboratory, 2018)
AbstractBackground Ascaris lumbricoides eggs had very thick walls consisted of three layers, they were albuminoid layer, hyaline layer and vitelin layer. These layers were impermeable causing the Ascaris lumbricoides eggs resistant to less supportive environmental factors. Formalin 10% was a preservative that was often used to preserve faeces containing parasites such as protozoa and worm eggs. However, without heating, formalin 10% was not effective to preserve the Ascaris lumbricoides eggs because they would keep developing to become infective (containing larvae). Objective This study aims to prove whether there is an effect of adding 10% formalin which is heated at 60 C, 70 C and 80 C to the development of Ascaris lumbricoides eggs.Methods The design of this research was an experimental study with The Randomized Posttest Control Group Design. Result The Ascaris lumbricoides eggs were still growing into infective eggs in faeces although they were heated by formalin 10% at 60C, 70C and 80C. conclusion Based on the results of the study, there was no effect of heating temperature of formalin 10% on the development of Ascaris lumbricoides egg.Keywords: Formalin 10%, Ascaris lumbricoides, Heating, Soil Transmitted Helminth